Misdiagnosis of Extraskeletal Osteochondroma in the Foot: A Report of 3 Cases. Issue 3 (22nd July 2022) - Lynch-Wong, Matthew; Wilson, Robert Alistair; Wong-Chung, John; Sharaf-Eldin, Osama
Abstract : Cases: Two women presented with newly growing callosities beneath the first and second metatarsal heads, initially believed to reflect gastrocnemius tightness and plantar plate pathology. In another man, swelling at the posterolateral aspect of the heel was mistaken for a Haglund deformity. Subsequent imaging of each patient led to delayed diagnosis of extraskeletal osteochondroma (ESO). Surgical excision resolved symptoms in all 3 with no recurrence over 12 months later. Conclusions: Whenever bony prominences newly develop in soft tissues of the foot, ESO should be suspected and appropriate imaging obtained. We describe physical features to help differentiate ESO from other common causes of foot overload.